A DltA Mutant of Haemophilus ducreyi Is Partially Attenuated in Its Ability To Cause Pustules in Human Volunteers - Janowicz, Diane (American Society for Microbiology, 2006)
Haemophilus ducreyi produces two outer membrane proteins, called DltA (H. ducreyi lectin A) and DsrA (H. ducreyi serum resistance A), that contribute to the ability of the organism to evade complement-mediated serum killing. In contrast to their isogenic parent strain, 35000HP, the DsrA mutant FX517 exhibits 0% survival in 50% normal human serum and the DltA mutant FX533 exhibits 23% survival. Compared to 35000HP, FX517 does not cause pustule formation in human volunteers. To test whether DltA was required for virulence in humans, seven volunteers were experimentally infected with 35000HP and FX533. Four subjects were inoculated with fixed doses of 35000HP (101 CFU or 130 CFU) at three sites on one arm and escalating doses of FX533 (range, 46 CFU to 915 CFU) at three sites on the other arm. Pustules only developed at mutant-injected sites at doses nearly twofold higher than that of the parent, suggesting that FX533 was partially attenuated. Three subjects were inoculated with similar doses of the parent (67 CFU) and mutant (104 CFU) at three sites. Pustules formed at five of nine parent sites and one of nine mutant sites. Overall, the papule and pustule formation rates for 35000HP and FX533 were similar for the trial. However, for the five subjects who received similar doses of the parent and mutant, pustules developed at 7 of 15 sites (46.7%; 95% confidence interval [CI], 16.9% to 76.5%) inoculated with the parent and at 1 of 15 (6.7%; 95% CI, 0.1% to 18.4%) sites inoculated with the mutant (P = 0.043). We concluded that the DltA mutant was attenuated in its ability to cause disease at doses similar to that of the parent.